Bivalve Feeding on the Brown Tide Aureoumbra lagunensis in a Shallow Coastal Environment - Galimany, Eve; Lunt, Jessica; Freeman, Christopher J.; Segura-García, I.; Mossop, M.; Domingos, A.; Houk, J.; Paul, Valerie J. (Frontiers in Marine Science, 2021)
Brown tides formed by Aureoumbra lagunensis decrease light penetration in the water column and are often followed by hypoxic events that result in the loss of fish and shellfish. To understand the ability of bivalve filter feeders to control and prevent A. lagunensis blooms, we exposed eastern oysters (Crassostrea virginica), hooked mussels (Ischadium recurvum), and hard clams (Mercenaria mercenaria) to a naturally co-occurring brown tide in the Indian River Lagoon (IRL), Florida, United States. Bivalves were exposed in the laboratory to multiple concentrations (104 to 106 cells mL–1) of isotopically labeled (13C and 15N) A. lagunensis cells. The standard clearance rate (herein clearance rate) of each bivalve species was calculated using flow cytometry to quantify A. lagunensis cell removal. The highest clearance rates were at 104 cells mL–1, but values varied across bivalve species (2.16 ± 0.30, 3.03 ± 0.58, and 0.41 ± 0.12 L h–1 for C. virginica, I. recurvum, and M. mercenaria, respectively). Although clearance rates decreased with increasing bloom concentrations, bivalves were still consuming algal cells at all concentrations and were retaining and assimilating more cells at the highest concentrations, as revealed by δ13C and δ15N values. We highlight interspecific differences among bivalve species in the removal of A. lagunensis, supporting the importance of healthy and diverse filter feeding communities in estuaries, especially as threats of brown tides and other HABs are increasing in the Anthropocene.